2022
DOI: 10.1002/hsr2.940
|View full text |Cite
|
Sign up to set email alerts
|

What has been learned about COVID‐19 vaccine hesitancy in Pakistan: Insights from a narrative review

Abstract: Background Vaccine hesitancy is not a new phenomenon to Pakistan. This is evidenced through the slow progress of previous vaccination campaigns and programs against MMR, BCG, and especially polio. This issue continues to persist and is therefore becoming the cause of low COVID‐19 vaccination rates in Pakistan. Aim To provide insights about COVID‐19 vaccine hesitancy among Pakistanis, and its potential harm on public health. Moreover, we aim provide recommendations to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Like other countries, vaccine hesitancy and low uptake are not new phenomena in Pakistan [49]. Vaccination campaigns and programs in the past have made slow progress, which is evidence of this: BCG (Bacillus Calmette Guerin) vaccination coverage was reported at 80%, polio vaccination coverage was 60%, and measles vaccination coverage was 67% [50].…”
Section: Study Areamentioning
confidence: 99%
“…Like other countries, vaccine hesitancy and low uptake are not new phenomena in Pakistan [49]. Vaccination campaigns and programs in the past have made slow progress, which is evidence of this: BCG (Bacillus Calmette Guerin) vaccination coverage was reported at 80%, polio vaccination coverage was 60%, and measles vaccination coverage was 67% [50].…”
Section: Study Areamentioning
confidence: 99%
“…Vaccine hesitancy is due to many factors. These include concerns with the safety and efficacy of the vaccine, lack of trust in healthcare services during the pandemic, and lack of trust in health authorities as well as disbelieving the reality of COVID-19 [ 54 , 55 , 56 , 57 , 58 ]. Whilst various studies from Pakistan have shown vaccine hesitancy in the general population [ 59 , 60 , 61 ], HCWs [ 62 , 63 ], pregnant women [ 64 ], and hospitalized COVID-19 patients [ 65 ], as well as (surprisingly) among patients undergoing hemodialysis [ 25 ], we are currently unaware of any study that has been undertaken among prisoners in Pakistan regarding their COVID-19 vaccine status.…”
Section: Introductionmentioning
confidence: 99%